Determination of the Spectrum of ETS Genes Expressed in Her2/Neu-Induced Mouse Mammary Tumors - Kockeritz, Lisa (My University, 1999)
The ets gene family of transcription factors has been widely implicated in a variety of human tumors. PEA3, the founding member of the PEA3 subfamily of ets genes is overexpressed in a mouse model of mammary tumorigenesis as well as in primary human breast tumors. PEA3 deregulation in these tumors is thought to increase the metastatic potential of mammary tumors by increasing the expression of various matrix metalloproteinases. The identification of other ets gene's expression using a mouse model of HER2/Neu-induced mammary tumorigenesis would provide insight into the mechanisms behind these mammary tumors. Degenerate RT-PCR analysis was used to screen for expression of all known ets genes in these tumors. A large spectrum of ets genes was identified as being expressed in these tumors. Quantitative analyses including semi-quantitative RT-PCR and ribonuclease protection assays, indicate that the PEA3 subfamily of ets genes, including PEA3, ERM and ER81, as being overexpressed in these tumors, while other ets genes, Ets-1, Ets-2 and GABP(alpha) were not. These results imply a specific role for the PEA3 subfamily in this model of mammary tumorigenesis and isolate this subfamily of ets genes as a possible therapeutic target.
Spectrum of ETS Genes Expressed in Her2/Neu-Induced Tumors
Keywords: ets; gene; spectrum; HER2; Neu; mouse; mammary tumor